Orthopaedic Society Leadership Diversity and Academic Participation: Where Do We Stand Now?. (21st December 2022) - Albright, Patrick; Banks, Evan; Wood, Lily; Chambers, Caitlin; Van Heest, Ann
Abstract : Background: In the United States, female and minority representation in the field of orthopaedic surgery remains low, and there are few reports regarding orthopaedic society leadership composition, selection criteria, and academic participation. We aimed to determine the demographic composition of national orthopaedic societies and report the academic participation metrics of leadership. Methods: This was a mixed-methods study using surveys and publicly available data from national orthopaedic societies for the 2020 to 2021 year. Twenty-four orthopaedic society websites were queried for their transparency in leadership selection and demographic information, including sex, racial, and ethnic composition of overall society and board membership. Data were collected regarding the academic participation of board leadership. Results: In total, 19 (79%) of the 24 national orthopaedic societies publish survey data regarding sex and racial demographics. One society elected not to participate, and there was no response from 4 others. Sixteen (89%) of the societies collect sex-related data from their membership, and 19 (100%) report sex-related data for their board members. Five (28%) collect data regarding the race and ethnicity of their general membership, and 10 (53%) report data regarding the race and ethnicity of board members. The average membership was 89% male and 11% female, and the leadership boards were 86% male and 14% female. In the societies that reported on race and ethnicity, on average, 80% of the members were White and 85% of the board members were White. Few societies (13%) publicly list their presidential nominating criteria, and none list their criteria for nonpresidential-line positions. Female sex and ≤10 years in practice were significantly associated with lower Hirsch index (h-index) scores, but these differences dissipated beyond 10 years. Conclusions: There is a lack of sex, racial, and ethnic diversity in orthopaedic society leadership. More robust recording of these data by societies can help track improvements in diversity among members and leaders. Academic participation may be one component of leadership selection, but other factors play an important role. Overall transparency of leadership selection criteria could be clarified among orthopaedic societies.